Exosome-educated macrophages and exosomes differentially improve ligament healing. (3rd November 2020) - Chamberlain, Connie S.; Kink, John A.; Wildenauer, Linzie A.; McCaughey, Maxwell; Henry, Katie; Spiker, Andrea M.; Halanski, Matthew A.; Hematti, Peiman; Vanderby, Ray
Abstract: Recently, our group used exosomes from mesenchymal stromal/stem cells (MSCs) to simulate an M2 macrophage phenotype, that is, exosome-educated macrophages (EEMs). These EEMs, when delivered in vivo, accelerated healing in a mouse Achilles tendon injury model. For the current study, we first tested the ability of EEMs to reproduce the beneficial healing effects in a different rodent model, that is, a rat medial collateral ligament (MCL) injury model. We hypothesized that treatment with EEMs would reduce inflammation and accelerate ligament healing, similar to our previous tendon results. Second, because of the translational advantages of a cell-free therapy, exosomes alone were also examined to promote MCL healing. We hypothesized that MSC-derived exosomes could also alter ligament healing to reduce scar formation. Similar to our previous Achilles tendon results, EEMs improved mechanical properties in the healing ligament and reduced inflammation, as indicated via a decreased endogenous M1/M2 macrophage ratio. We also showed that exosomes improved ligament remodeling as indicated by changes in collagen production and organization, and reduced scar formation but without improved mechanical behavior in healing tissue. Overall, our findings suggest EEMs and MSC-derived exosomes improve healing but via different mechanisms. EEMs and exosomes each have attractive characteristics as therapeutics. EEMs as a cell therapy are terminally differentiated and will not proliferate or differentiate. Alternatively, exosome therapy can be used as a cell free, shelf-stable therapeutic to deliver biologically active components. Results herein further support using EEMs and/or exosomes to improve ligament healing by modulating inflammation and promoting more advantageous tissue remodeling. Abstract : Exosome-educated macrophages (EEMs) and exosomes differentially improve ligament healing. EEM treatment to an injured rat medial collateral ligament resulted in reduced inflammation and improved ligament strength. In contrast, exosome treatment reduced scar size, and increased collagen organization and production. Despite different outcomes, both treatments were uniquely effective in accelerating healing.